2008
DOI: 10.3390/ijms9030327
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Berries and Ellagic Acid Prevent Oxidative DNA Damage and Modulate Expression of DNA Repair Genes

Abstract: DNA damage is a pre-requisite for the initiation of cancer and agents that reduce this damage are useful in cancer prevention. In this study, we evaluated the ability of whole berries and berry phytochemical, ellagic acid to reduce endogenous oxidative DNA damage. Ellagic acid was selected based on >95% inhibition of 8-oxodeoxyguosine (8-oxodG) and other unidentified oxidative DNA adducts induced by 4-hydroxy-17ß-estradiol and CuCl 2 in vitro. Inhibition of the latter occurred at lower concentrations (10 µM) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 41 publications
6
33
0
3
Order By: Relevance
“…Pterostilbene, primarily found in blueberries, is an antioxidant that acts as an effective anticancer agent in various common malignancies, including breast and colon cancer (20). In addition, ellagic acid has been associated with the prevention of oxidative DNA damage and modulation of DNA repair gene expression (21). These components interact and influence biological processes in the human body, resulting in the potentially protective and preventive actions of blueberries.…”
Section: Discussionmentioning
confidence: 99%
“…Pterostilbene, primarily found in blueberries, is an antioxidant that acts as an effective anticancer agent in various common malignancies, including breast and colon cancer (20). In addition, ellagic acid has been associated with the prevention of oxidative DNA damage and modulation of DNA repair gene expression (21). These components interact and influence biological processes in the human body, resulting in the potentially protective and preventive actions of blueberries.…”
Section: Discussionmentioning
confidence: 99%
“…Aiyer et al [49] fed mice a diet containing either ellagic acid (a polyphenol found in many berries), or dehydrated blueberry, strawberry or raspberry. Ellagic acid and raspberry had particularly strong effects, increasing mRNA levels of Xpa, Ercc5 and Dnl3 (DNA ligase III) by three-to eightfold.…”
Section: Animal Studies Of the Effect Of Micronutrients On Dna Repairmentioning
confidence: 99%
“…For the preparations of the BB and BRB diet, AIN 93M diet was powdered and mixed with BB and BRB powder at 5% and 2.5% (w/w), respectively, and stored at 4 • C until use. The diets were isocaloric and the recipe used was the same as described by us elsewhere [8,16,17].…”
Section: Dietmentioning
confidence: 99%